Implant Anchorage in Orthodontic Retrusion: A Case Report - Camelia Szuhanek; Adelina Grigore (Journal of Dentistry And Oral Implants, 2019)
Mini screws represent a new treatment modality in orthodontic biomechanics. They provide absolute anchorage, no secondary movements and reduced orthodontic treatment time. Futhermore, the surgical procedure for mini implants placement is quite simple and this type of treatment requires no patient compliance. We selected a clinical case in order to emphasize one of the most important indications of the mini implants: retrusion of the upper incisors for a incresed overjet case in a young patient. Two mini implants were placed in order to obtain the correction of the overjet and the retrusion of the anterior teeth. The retrusion was obtained in a reduced period of time using retraction devices on crimpable hooks.
Keywords: Orthodontic implants